The nexus between external debt, corruption and economic growth: evidence from five SSA countries - Shittu, Waliu Olawale; Hassan, Sallahuddin; Nawaz, Muhammad Atif (Emerald Publishing Limited, 2018)
Purpose: The purpose of this paper is to examine the impact of external debt and corruption on economic growth in the selected five Sub-Saharan African (SSA) countries, from 1990 to 2015. Design/methodology/approach: Panel unit root and panel cointegration tests are employed to test for stationarity of the series and the long-run relationship, respectively. Fully modified OLS and dynamic OLS techniques are also employed to examine the long-run coefficients of the variables of the model, as well as panel Granger causality test, in order to examine the direction of causality among the variables. Findings: The results indicate that there is a negative relationship between external debt and economic growth, as well as a bi-directional causality between the two variables. The findings also indicate a positive relationship between corruption and economic growth, as well as a uni-directional causality running from economic growth through corruption. Research limitations/implications: The study recommends that the governments of the selected countries should address the menace of rising external debt through the adoption of other sources of capital for investment. Such include more openness of the economy for more capital, by easing restrictions on genuine imports and exports of valuable goods and services. It also suggests that the issue of corruption be tackled head-on, by such penalties that tend to make corruption less attractive. Originality/value: While the relationship between economic growth and external debt, on the one hand, and corruption and economic growth, on the other hand, have received considerable attentions, the trio of external debt, corruption and economic growth have not been found combined in a model, to the best of the authors’ knowledge. Also, the countries under consideration, who jointly account for about 47 percent of the entire SSA countries’ stock of external debt, have not been jointly found in any recent panel studies involving the selected variables.